Co-constructing loyalty in an era of digital music fandom: An experiential-discursive perspective. (20th February 2019) - Obiegbu, Chinedu James; Larsen, Gretchen; Ellis, Nick; O'Reilly, Daragh
Abstract : Purpose: This paper aims to answer the following question: How can a discursive approach to how music fans construct loyalty in a digital context contribute to a theoretical understanding of brand loyalty? Design/methodology/approach: Drawing on insights from theories of brand loyalty and fandom, this interpretive inquiry makes use of data from an online forum dedicated to the rock music band, U2, and interviews with forum members. A combination of online ethnography and discourse analysis are used. Findings: The analysis shows that music fans mobilise particular discursive resources in constructing loyalty in the digital context, specifically length of time spent as a fan, obsession and the opposition of obligation and choice. These discursive resources reflect a grounded account of an experientially rooted brand loyalty that extends beyond attitudinal and behavioural loyalty and which is particularly salient in music consumption. Research limitations/implications: This is a single case study, but as a rich and vibrant online community, it provides fruitful insights into the discursive construction of loyalty. The processes of negotiation, accommodation and conflict, engaged in through online discourse, are important in laying bare the preferences, value systems and meanings that frame the experiences of loyal consumers. Practical implications: This socially constructed view of loyalty facilitates a more sensitive and nuanced application of brand loyalty, with implications for segmentation and targeting activities. It provides a possible basis through which precise insights can be gained into the meanings and practices of loyal fans and consumers. Originality/value: Examining loyalty through the lens of online music fandom enables a discursive understanding of consumers' experience of brand loyalty. It shows how online engagement with other consumers of a brand facilitates a deep engagement with the notion of loyalty.